2016
DOI: 10.1002/hbm.23306
|View full text |Cite
|
Sign up to set email alerts
|

The impact of parkinson's disease on the cortical mechanisms that support auditory–motor integration for voice control

Abstract: Several studies have shown sensorimotor deficits in speech processing in individuals with idiopathic Parkinson's disease (PD). The underlying neural mechanisms, however, remain poorly understood. In the present event-related potential (ERP) study, 18 individuals with PD and 18 healthy controls were exposed to frequency-altered feedback (FAF) while producing a sustained vowel and listening to the playback of their own voice. Behavioral results revealed that individuals with PD produced significantly larger voca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
86
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 68 publications
(108 citation statements)
references
References 74 publications
(191 reference statements)
18
86
4
Order By: Relevance
“…Abnormal vocal behavior towards altered auditory feedback was also reported in patients with Parkinson's disease in several previous experiments (Chen, et al, 2013,Huang, et al, 2016,Liu, et al, 2012,Mollaei, et al, 2013). Like the AD patients in the current study Patients with Parkinson's disease also showed an elevated pitch-compensatory response (Chen, et al, 2013,Huang, et al, 2016).…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Abnormal vocal behavior towards altered auditory feedback was also reported in patients with Parkinson's disease in several previous experiments (Chen, et al, 2013,Huang, et al, 2016,Liu, et al, 2012,Mollaei, et al, 2013). Like the AD patients in the current study Patients with Parkinson's disease also showed an elevated pitch-compensatory response (Chen, et al, 2013,Huang, et al, 2016).…”
Section: Discussionsupporting
confidence: 67%
“…Like the AD patients in the current study Patients with Parkinson's disease also showed an elevated pitch-compensatory response (Chen, et al, 2013,Huang, et al, 2016). Further, the Parkinson's disease patients also showed an elevated amplitude-compensatory response in experiments where amplitude was perturbed in the feedback signal (Liu, et al, 2012).…”
Section: Discussionsupporting
confidence: 56%
“…The STG cluster identified in the present study corresponds closely to an anterolateral region of Heschl's gyrus that electrocorticography data has linked to online voice error correction following rapid perturbations in auditory feedback (Behroozmand et al., 2016). Compared to healthy individuals, those with PD respond to rapid perturbations in auditory feedback with an exaggerated compensation in vocal output compared to healthy controls (Chen et al., 2013; Huang et al., 2016; Liu, Wang, Metman, & Larson, 2012). It has thus been suggested that people with PD have impaired feedforward control of speech production and, as a result, rely more heavily on sensory feedback integration (Liu et al., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings raise the possibility that, in addition to impaired feedforward control, there may be impaired auditory feedback integration mediated by decreased connectivity between left putamen and left STG. For example, not only do people with PD respond to rapid auditory perturbations with exaggerated vocal responses (Chen et al., 2013; Huang et al., 2016; Liu et al., 2012), they also appear to compensate less than controls when adapting to long‐term alterations in auditory feedback (Mollaei, Shiller, & Gracco, 2013). Decreased coupling of left putamen and left STG could thus reflect difficulties in integrating sensory information during speech production in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence has shown that P2 component reflects not only the central auditory processing (e.g., error detection) but also the feedback-based motor processing (e.g., error correction) in the online monitoring of vocal production. For example, when compensating for pitch perturbations in voice auditory feedback, individuals with Parkinson's disease produced significantly larger P2 responses than healthy controls due to enhanced activity in the brain regions including the STG, PMC, and IFG (Huang et al, 2016). Also, P2 responses were found to be significantly correlated with regional homogeneity of those brain regions in the resting-state (Guo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%